Case study on the premier showing of my blue heaven - Flores, Ana Maria; Pandan, Mary Ann; Leano, Hanzel (Quezon City UP College of Engineering, 1991)
This study aimed at setting the plan of activities made by the UP Chemical Engineering Society on their premier showing of My Blue Heaven.It also analyze the problems encountered and corresponding alternatives or solution to these problems.From the data gathered by interviews and surveys it was found that the scheduling activity was good.In the implementation of the scheduled activities the organization was efficient. However,improvements are suggested. Based on the surveys,patrons to be shown.It was also found out that finding a good fil at the right time is not easy.A lot of waiting was needed and this gave a shorter time from the promotion and selling of tickets.It was also found out that being a first timer in this venture the organizers faced certain difficulties.For instance major sponsors were reluctatnt to invest on this project,No strong connections were available.So it is suggested that if more people are working for this project it will be better because of time constraints.
Feasibility study.
Submitted in partial fulfillment of the course requirements in IE 3: Introduction to Industrial Engineering
Keywords: Special events -- Management -- Philippines; Special events -- Marketing -- Philippines